Beyond the Game: Unpacking Fan Interaction of Indonesian and Filipino in MSC 2022 and 2023 YouTube Comments - Airlangga Daniswara; Moch Fuad Nasvian (ULTIMA Comm, 2024)
The rise of esports, particularly the Mobile Legends: Bang bang South East Asia Cup (MSC), has witnessed immense popularity in the Southeast Asian region. This study explores the nature and depth of fan interactions from two significant contributors to the MSC fandom, Indonesia and the Philippines, throughout the 2022 and 2023 championships. Utilizing YouTube comments as a primary data source, this research delves into the patterns of fan interaction, aiming to understand the nuances of digital interactivity and fandom dynamics in these two nations. Our analysis reveals significant insights into how Indonesian and Filipino fans perceive the games, express their fandom, and engage with one another during MSC events. This study provides a granular understanding of fan culture in esports, shedding light on the importance of digital platforms like YouTube in shaping the landscape of modern fandom interactions. Furthermore, the findings also have implications for event organizers, game developers, and marketing strategists in their endeavors to maximize fan engagement and foster positive community dynamics.